Notas de Jean-Jaques Rousseau, Carlos Enrique Carolano, Carlos S. Nino, Isabel Beatriz Russo y Enrique Domingo Valle - Carolano, Carlos Enrique; Rousseau, Jean-Jacques; Nino, Carlos Santiago; Russo, Isabel Beatriz; Valle, Enrique Domingo (Lecciones y Ensayos, 1967)